Genome-Wide Insight into Profound Effect of Carbon Catabolite Repressor (Cre1) on the Insect-Pathogenic Lifecycle of Beauveriabassiana - Rehab Abdelmonem Mohamed (MDPI AG, 2021)
Carbon catabolite repression (CCR) is critical for the preferential utilization of glucose derived from environmental carbon sources and regulated by carbon catabolite repressor A (Cre1/CreA) in filamentous fungi. However, a role of Cre1-mediated CCR in insect-pathogenic fungal utilization of host nutrients during normal cuticle infection (NCI) and hemocoel colonization remains explored insufficiently. Here, we report an indispensability of Cre1 for Beauveriabassiana’s utilization of nutrients in insect integument and hemocoel. Deletion of cre1 resulted in severe defects in radial growth on various media, hypersensitivity to oxidative stress, abolished pathogenicity via NCI or intrahemocoel injection (cuticle-bypassing infection) but no change in conidial hydrophobicity and adherence to insect cuticle. Markedly reduced biomass accumulation in the Δcre1 cultures was directly causative of severe defect in aerial conidiation and reduced secretion of various cuticle-degrading enzymes. The majority (1117) of 1881 dysregulated genes identified from the Δcre1 versus wild-type cultures were significantly downregulated, leading to substantial repression of many enriched function terms and pathways, particularly those involved in carbon and nitrogen metabolisms, cuticle degradation, antioxidant response, cellular transport and homeostasis, and direct/indirect gene mediation. These findings offer a novel insight into profound effect of Cre1 on the insect-pathogenic lifestyle of B. bassiana.